Cross Acclimation between Heat and Hypoxia: Heat Acclimation Improves Cellular Tolerance and Exercise Performance in Acute Normobaric Hypoxia - Lee, Ben J.; Miller, Amanda; James, Rob S.; Thake, Charles D. (Frontiers in Physiology, 2016)
Background. The potential for cross acclimation between environmental stressors is not well understood. Thus the aim of this investigation was to determine the effect of fixed-workload heat or hypoxic acclimation on cellular, physiological and performance responses during post acclimation hypoxic exercise in humans. Method. Twenty-one males (age 22 ± 5 years; stature 1.76 ± 0.07m; mass 71.8 ± 7.9kg; V ̇O2 peak 51 ± 7mL.kg-1.min-1) completed a cycling hypoxic stress test (HST) and self-paced 16.1km time trial (TT) before (HST1, TT1), and after (HST2, TT2) a series of 10 daily 60 min training sessions (50% N V ̇O2peak) in control (CON, n = 7; 18°C, 35%RH), hypoxic (HYP, n = 7;) or hot (HOT, n = 7; 40°C, 25% RH) conditions. Results. TT performance in hypoxia was improved following both acclimation treatments, HYP (-3:16 ± 3:10 mins:sec; p = 0.0006) and HOT (-2:02 ± 1:02 mins:sec; p = 0.005), but unchanged after CON (+0:31 ± 1:42 mins:sec). Resting monocyte heat shock protein 72 (mHSP72) increased prior to HST2 in HOT (62 ± 46%) and HYP (58 ± 52%), but was unchanged after CON (9 ± 46%), leading to an attenuated mHSP72 response to hypoxic exercise in HOT and HYP HST2 compared to HST1 (p < 0.01). Changes in extracellular hypoxia-inducible factor 1-α followed a similar pattern to those of mHSP72. Physiological strain index (PSI) was attenuated in HOT (HST1 = 4.12 ± 0.58, HST2 = 3.60 ± 0.42; p = 0.007) as a result of a reduced HR (HST1 = 140 ± 14 b.min-1; HST2 131 ± 9 b.min-1 p = 0.0006) and Trectal (HST1 = 37.55 ± 0.18°C; HST2 37.45 ± 0.14°C; p = 0.018) during exercise. Whereas PSI did not change in HYP (HST1 = 4.82 ± 0.64, HST2 4.83 ± 0.63). Conclusion. Heat acclimation improved cellular and systemic physiological tolerance to steady state exercise in moderate hypoxia. Additionally we show, for the first time, that heat acclimation improved cycling time trial performance to a magnitude similar to that achieved by hypoxic acclimation.